2012
DOI: 10.1097/shk.0b013e318257114e
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Nitric Oxide and Reactive Oxygen Species by Neutrophils and Monocytes From Septic Patients and Association With Outcomes

Abstract: In this study, our aims were to evaluate the reactive oxygen species (ROS) and nitric oxide (NO) generation by monocytes and neutrophils from septic patients and to correlate their levels with clinical outcomes. Forty-nine septic patients and 19 healthy volunteers were enrolled in the study. The ROS and NO production was quantified in monocytes and neutrophils in whole blood by flow cytometry, constitutively, and after stimulation with Staphylococcus aureus and Pseudomonas aeruginosa. Nitric oxide production b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 33 publications
7
66
0
3
Order By: Relevance
“…Studies of the role of monocytes in patients with severe sepsis and septic shock have revealed a hyporesponsive state characterized by low production of inflammatory cytokines in the peripheral blood cells of patients with sepsis upon restimulation in vitro (11)(12)(13). We have demonstrated that monocytes from patients with sepsis, which are hyporesponsive for the production of TNF-a (14,15), retain the ability to generate ROS and NO (1,16,17), similar to LPS-tolerant cells. Furthermore, genes belonging to the toll-like receptor (TLR) signaling pathways are dynamically modulated during sepsis (18,19) in a manner similar to that observed in LPS-tolerant human mononuclear cells (reviewed in Refs.…”
mentioning
confidence: 80%
“…Studies of the role of monocytes in patients with severe sepsis and septic shock have revealed a hyporesponsive state characterized by low production of inflammatory cytokines in the peripheral blood cells of patients with sepsis upon restimulation in vitro (11)(12)(13). We have demonstrated that monocytes from patients with sepsis, which are hyporesponsive for the production of TNF-a (14,15), retain the ability to generate ROS and NO (1,16,17), similar to LPS-tolerant cells. Furthermore, genes belonging to the toll-like receptor (TLR) signaling pathways are dynamically modulated during sepsis (18,19) in a manner similar to that observed in LPS-tolerant human mononuclear cells (reviewed in Refs.…”
mentioning
confidence: 80%
“…Serum levels of nitric oxide and cytokines including IL-1b and TNF-a have been reported increased in patients with sepsis (Krüttgen & Rose-John, 2012;Santos et al, 2012). It was shown that in vitro synthesis of EPO in cell cultures is suppressed by TNF-a and IL-1 (Nakamura et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that emerging oxidative stress and cell damage following increased production of prostaglandins, nitric oxide, free radicals and pro-inflammatory cytokines such as tumor necrosis factor-a (TNF-a) and interleukin-1b (IL-1b) are responsible for the multiple organ failures and deaths caused by sepsis (Beutler & Poltorak, 2001;Krüttgen & Rose-John, 2012). Nitric oxide is an important source for the production of powerful free radicals and has also direct deleterious effects on cells during sepsis (Santos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They thought the mechanism was that DTC blocked endothelium-derived relaxing factors (EDRF) including NO. Indeed, many studies reported that NO was generated markedly in sepsis animal models and septic patients [22,23,24]. Based on that copper stimulated NO production [8,9,10], it was reasonable to speculate that copper might be involved in the vascular hyporeactivity in sepsis through enhancing NO action.…”
Section: Discussionmentioning
confidence: 99%